Cardiac Hypertrophy in obesity: Leptin-TRH interaction - Aisicovich, Maia (2018)
Cardiac TRH induce left ventricular hypertrophy (LVH) and fibrosis, its inhibition prevent hypertrophy.The adiponectin leptin induces TRH in CNS. We hypothesized that in obesity, the increase of TRH induced by hyperleptinemia is responsible of the LVH, until now mostly attributed to pressure load. We studied obese Agouti mice suffering hypertension with hyperleptinemia and found LVH with increased TRH gene expression. Consequently we found higher (p<0.05) fibrotic and hypertrophic markers vs lean (BL/6J). As pressure could explain results we treated obese mice with diuretic (hydroclorothiazide 20 mg/kg/day) from weaning (n=9), the diuretic group was normotensive in contrast to control obese mice. Nevertheless both groups developed (p<0.05): LVH, higher TRH gene and elevated fibrotic and hypertrophic markers suggesting that LVH is not induced by hypertension. In contrast to Agouti, we studied obese Ob/Ob mice lacking leptin due to a disruption in their gene. Mice are normotensive, without LVH despite their obesity. We treated 2 groups with leptin (sc. 80 ug/kg/day) or saline from weaning for 15 days. Only the group treated with leptin developed LVH (LV weight/tibia length, p< 0.05, n=7) vs saline, pointing out that LVH is leptin dependant. As hypothesized, in this group we found an increase (p<0.05) in cardiac TRH accompanied by higher expression of type III collagen suggesting that leptin-TRH interaction is required for obesity-induced LVH. To confirm cardiac cells TRH´s leptin induction, cardiomyocytes derived cell line H9C2 (n=6) was stimulated with leptin (10 and100 ng/ml). TRH expression (rt-PCR) and peptide (WB) were increased (p<0.05) post leptin at both concentrations. Moreover we developed cardiomiocytes primary culture from neonates, in which leptin stimulus (80 ng/ml, 24 hs) increased (p<0.05) TRH content vs controls confirming the direct TRH induction by leptin in heart cells. Finally, obese-induced LVH is leptin-dependent, who probably stimulates hypertrophy and fibrosis by its TRH induction.